Nonsecretory Multiple Myeloma and AL Amyloidosis Presenting with Nephrotic Range Proteinuria - Ozlem Beyler Kilic; Ali Kemal Oguz; Ihsan Ergun; Dilek Ertoy Baydar; Meltem Ayli (Case Reports in Nephrology)
Nonsecretory multiple myeloma (NSMM) is the absence of a detectable monoclonal protein in serum and urine of a multiple myeloma (MM) patient and immunoglobulin light chain (AL) amyloidosis is a significantly rare complication. A case of NSMM with AL amyloidosis and nephrotic range proteinuria is presented. Sharing clinical, therapeutic, and prognostic characteristics with MM, real challenge may be during initial diagnosis of NSMM and assessment of treatment response. In elderly patients with unexplained renal dysfunction, MM should be in the differential diagnosis and the absence of a monoclonal protein should not rule out MM but should remind us of the possibility of NSMM.